Membangun Identitas Inklusif - Krisis Identitas Dalam Lensa Kajian Poskolonialisme - Robertus Wijanarko (Seri Filsafat Teologi, 2020)
Multidimentional crisis which became more visible in the Covid-19 pademic era, actually rooted in the crisis of identity of Indonesia. It occurs, especially when identitys is considered as essential caracters or inherent features of this nation, inherited from the previous generation. The understanding of such kind of identity causes defensive, exclusive attitudes at the level of individual, communal, or even as a nation. In this perspective life is simply considered as an arena of contestation and will end up in the subordination of the others. By utilizing the lens of Postcolonial Theory, I axhibit the roots of that crisis of identity, and also propose a new perspective, which is comprehending identity as a production or a continuous process in a making. This new understanding of identity, I believe, will enable Indonesia to cope with the crisis, and to find ethical foundations in preserving and cultivating their life inclusively.